New Carabid Species (Coleoptera, Carabidae) for the Fauna of Dagestan - I. I. Kabak; I. A. Belousov; G. M. Nakhibasheva; E. V. Ilyina (Юг России: экология, развитие, 2020)
Aim. To present new data on the distribution of Carabid species in Dagestan, Russia. Material and Methods. The paper is based on material collected in the lowland areas of Dagestan. Conventional sampling techniques were used: hand collecting, UV light traps and pitfall traps.Results. The three following species of Carabidae have been found in Dagestan for the first time: Poecilus (s. str.) anodon (Chaudoir, 1868), Pterostichus (Platysma) planicollis (Tschischerine, 1898) and Diplocheila (Isorembus) transcaspica (Semenov, 1891), with the latter being a new species for the fauna of Russia. New distributional records have been mapped. Photographs of all three species are provided.Conclusion. These new distributional data are unlikely to be explained within the context of global warming since, for two of the three species under consideration, Poecilus anodon and Pterostichus planicollis, the ranges of distribution are located largely north of the study area.